BMP4 regulates the hematopoietic stem cell niche - Goldman, Devorah C. (American Society of Hematology, 2009)
Bone morphogenetic protein 4 (BMP4) is required for mesoderm commitment to the hematopoietic lineage during early embryogenesis. However, deletion of BMP4 is early embryonically lethal and its functional role in definitive hematopoiesis is unknown. Consequently, we used a BMP4 hypomorph to investigate the role of BMP4 in regulating hematopoietic stem cell (HSC) function and maintaining steady-state hematopoiesis in the adult. Reporter gene expression shows that Bmp4 is expressed in cells associated with the hematopoietic microenvironment including osteoblasts, endothelial cells, and megakaryocytes. Although resting hematopoiesis is normal in a BMP4-deficient background, the number of c-Kit(+), Sca-1(+), Lineage(−) cells is significantly reduced. Serial transplantation studies reveal that BMP4-deficient recipients have a microenvironmental defect that reduces the repopulating activity of wild-type HSCs. This defect is even more pronounced in a parabiosis model that demonstrates a profound reduction in wild-type hematopoietic cells within the bone marrow of BMP4-deficient recipients. Furthermore, wild-type HSCs that successfully engraft into the BMP4-deficient bone marrow show a marked decrease in functional stem cell activity when tested in a competitive repopulation assay. Taken together, these findings indicate BMP4 is a critical component of the hematopoietic microenvironment that regulates both HSC number and function.